Corrigendum to “Cytokine expression and Mycoplasma hyopneumoniae burden in the development of lung lesions in experimentally inoculated pigs” [Vet. Microbiol. 244 (2020) 108647] (Veterinary Microbiology (2020) 244, (S0378113519314646), (10.1016/j.vetmic.2020.108647)) - Almeida, Henrique M.S. [UNESP]; Mechler-Dreibi, Marina L. [UNESP]; Sonálio, Karina [UNESP]; Ferraz, Maria Eugênia S. [UNESP]; Storino, Gabriel Y. [UNESP]; Barbosa, Fernanda O. [UNESP]; Maes, Dominiek; Montassier, Hélio J. [UNESP]; de Oliveira, Luis G. [UNESP] (Elsevier, 2020)
The authors regret that mistakes were not noted during the proof correction of the original article. Consequently, we would like to publish this corrigendum linked to the article indicated. 1 In the “Macroscopic Lung Lesion Score” column of Table 3 there should be only one * in both p-values, instead of **.2 Funding: The authors would like to acknowledge the São Paulo State Research Support Foundation (FAPESP) for providing funds for this study (Grants #2016∕18698-2 and #2019/19710-4).The authors would like to apologise for any inconvenience caused.